Professional competencies and the continuing professional development needs of Technical, Vocational Education and Training (TVET) teachers in Kenya - Njenga, Moses (Hungarian Educational Research Journal, 2022)
The development of Continuing Professional Development (CPD) programs for vocational teachers in Africa has been hampered by a lack of relevant research on their CPD practices and learning needs. This study therefore investigated the learning needs of vocational teachers in Kenya based on the professional competencies vocational teachers identify as essential for their work and their self-perception of competence. Using a concurrent mixed methods approach, data was collected from 170 questionnaire respondents and sixteen interview participants from six Technical, Vocational Education and Training (TVET) institutions in Kenya. Despite TVET teachers perceiving themselves as highly competent, they were found to express a relatively high need for CPD. The need was most strongly expressed by teachers who had received Initial Teacher Education (ITE), which suggested that ITE has a positive influence in sensitising teachers on the need for CPD. New teachers were however found to have a lower perception of competence. Mentorship for new teachers is thus recommended. An unexpected finding was that while TVET teachers in Kenya identify good teaching skills as an essential competency for vocational teachers, they assume mastery of content translates to good teaching skills. It is thus recommended that the curriculum for TVET teachers in Kenya be reviewed to help teachers appreciate, identify, and develop subject-specific teaching skills.
Keywords: self assessment; professional competencies; vocational teachers; Kenya; continuing professional development